Phosphodiesterase Inhibitors : Alternatif Pengobatan Lower Urinary Tract Symptomps yang disebabkan Benign Prostate Hyperplasia - Fahmi Ikhtiar; Exsa Hadibrata (CV. Jasa Sukses Abadi, 2023)
Lower urinary tract symptoms (LUTS) secondary to benign prostatic hyperplasia (BPH) are often bothersome and hinder the quality of life for eldery. The incidence of BPH in Indonesia, namely at Cipto Mangunkusumo Hospital from 1994-2013, found 3,804 cases with an average age of patients 66.61 years. Adrenoceptor antagonists (α‑blockers, ABs) and 5-Alpha reductase Inhibitors (5-ARIs) are recommended first-line treatment for LUTS due to BPH. Although effective, these medications may have adverse effects, including dizziness, hypotension, and sexual dysfunction. Phosphodiesterase 5 Inhibitors (PDE5-Is) have been used globally as first-line drugs for erectile dysfunction. The first study in 2002 reported that PDE5‑Is could improve urinary tract symptom scores in patients w